Workplace substance testing --an exploratory study - Jain, Harish C.; Zeytinoglu, Isik U.; Piczak, Michael; McMaster University, Michael G. DeGroote School of Business (My University, 1997)
This study, using 1993 survey data taken from large Ontario, Canada, headquartered organizations (n = 127), compares workplace substance testing versus non-testing organizations based on a number of external and internal factors. Results showed that few Canadian organizations conduct workplace substance testing. Variables such as sector, location of operations, risk sensitivity and organizational structure appear to be not related to the workplace substance testing decision. Partial support was found for age and size of organization (measured in sales volume) as differentiating workplace substance testing organizations from non-testers. Public policy implications based on these findings are provided.
27 leaves : ; Includes bibliographical references (leaves 25-27). ; "November, 1997".
This research was funded by the Arts Research Board of McMaster University. Forthcoming, in March 1998, in Employee Rights and Responsibilities Journal.
Keywords: Workplace substance testing; Empirical study; Policy implications; Business; Business; Employees > Drug testing Employees > Substance use